2016
DOI: 10.1038/srep24493
|View full text |Cite
|
Sign up to set email alerts
|

Osmotin attenuates LPS-induced neuroinflammation and memory impairments via the TLR4/NFκB signaling pathway

Abstract: Toll-like receptor 4 (TLR4) signaling in the brain mediates autoimmune responses and induces neuroinflammation that results in neurodegenerative diseases, such as Alzheimer’s disease (AD). The plant hormone osmotin inhibited lipopolysaccharide (LPS)-induced TLR4 downstream signaling, including activation of TLR4, CD14, IKKα/β, and NFκB, and the release of inflammatory mediators, such as COX-2, TNF-α, iNOS, and IL-1β. Immunoprecipitation demonstrated colocalization of TLR4 and AdipoR1 receptors in BV2 microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
158
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(167 citation statements)
references
References 52 publications
9
158
0
Order By: Relevance
“…In addition, there is a good correlation between the structure and function of the pyramidal cells in hippocampus and cortex and learning and memory functions . Histological observations of mouse brains showed damage to the pyramidal cells in hippocampus and cortex after LPS injections, characterized by extensive loss of Nissl substance and normal neuronal cells, which were consistent with previous studies . Aromatic‐turmerone administration could reverse this pathological change.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there is a good correlation between the structure and function of the pyramidal cells in hippocampus and cortex and learning and memory functions . Histological observations of mouse brains showed damage to the pyramidal cells in hippocampus and cortex after LPS injections, characterized by extensive loss of Nissl substance and normal neuronal cells, which were consistent with previous studies . Aromatic‐turmerone administration could reverse this pathological change.…”
Section: Discussionsupporting
confidence: 90%
“…Though there is still no information on whether APN can regulate microglia activation, a recent report has demonstrated that microglia expressed adiponectin receptors. Osmotin, plant homolog of adiponectin, inhibited Toll-like receptor 4 (TLR4) in microglia cell line BV2 through AdipoR1 to prevent LPS-induced inflammation [49]. Moreover, astrocytes and macrophages also possess APN receptors and being stimulated by APN, suggesting that APN can regulate both cerebral and peripheral inflammation [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely therefore that immunohistochemistry is not sensitive enough to detect the basal cellular expression of TLR4. Moreover, in vitro experiments demonstrated that LPS can rapidly induce TLR4 in both CNS and non CNS cell types [61-63]. …”
Section: Discussionmentioning
confidence: 99%